Readability, Understandability and Actionability of Online Cardiovascular Risk Assessment Tools and Patient Educational Material: A Systematic Review - Ashraf Roshan; Jason Choo; Cynthia Ciwei Lim (Glomerular Diseases, 2022)
Background: Individuals with kidney diseases have increased risk of cardiovascular disease and death. Online cardiovascular risk assessment tools can educate patients on risks and modifiable factors. Since patients have variable health literacy, we evaluated the readability, understandability and actionability of publicly available online cardiovascular risk assessment tools.